Chaotic neural networks and the traveling salesman problem - Yamada, T.; Aihara, K.; Kotani, M. (International Joint Conference on Neural Networks, Nagoya, 1993, 1993)
Deterministic chaos is not only a profound scientific concept but also ubiquitously found in both natural and artificial real-world systems. From the viewpoint of engineering, the deterministic chaos has many possible applicabilities. In this report, the authors study the application of chaotic neural networks (CNN) to the traveling salesman problem (TSP) as a concrete example of possible application of deterministic chaos. First, a neuron model with chaotic dynamics, which comprises CNN as the element, is explained and its nonlinear dynamics are demonstrated. Second, the network representations for neurocomputing approaches to TSPs are described. Last, it is shown that CNN have high ability to solve TSPs.